2019
DOI: 10.1177/0956797618822697
|View full text |Cite
|
Sign up to set email alerts
|

Perspective Taking and Self-Persuasion: Why “Putting Yourself in Their Shoes” Reduces Openness to Attitude Change

Abstract: Counterattitudinal-argument generation is a powerful tool for opening people up to alternative views. On the basis of decades of research, it should be especially effective when people adopt the perspective of individuals who hold alternative views. In the current research, however, we found the opposite: In three preregistered experiments (total N = 2,734), we found that taking the perspective of someone who endorses a counterattitudinal view lowers receptiveness to that view and reduces attitude change follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 37 publications
(23 reference statements)
2
29
0
Order By: Relevance
“…For example, participants are taught techniques, such as "putting oneself in another's shoes" (perspective-taking), thinking of people from other groups as individuals rather than just as homogeneous group members (individuation), and generating examples of people from other groups who challenge stereotypical assumptions (e.g., Marie Curie; counterstereotype exposure). While some of these strategies have shown mixed effects when implemented in isola-tion, especially perspective-taking (Catapano et al, 2019) and intergroup contact (Paluck et al, 2018), the combination of strategies, coupled with the educational approach, shows promise in addressing gender disparities in STEM.…”
Section: Changing Individual-level Gender Biasmentioning
confidence: 99%
“…For example, participants are taught techniques, such as "putting oneself in another's shoes" (perspective-taking), thinking of people from other groups as individuals rather than just as homogeneous group members (individuation), and generating examples of people from other groups who challenge stereotypical assumptions (e.g., Marie Curie; counterstereotype exposure). While some of these strategies have shown mixed effects when implemented in isola-tion, especially perspective-taking (Catapano et al, 2019) and intergroup contact (Paluck et al, 2018), the combination of strategies, coupled with the educational approach, shows promise in addressing gender disparities in STEM.…”
Section: Changing Individual-level Gender Biasmentioning
confidence: 99%
“…The effectiveness of choice blindness in the political domain distinguishes it from many other forms of persuasion, such as perspective-taking [55][56]. In a recent study, Catapano and colleagues [57] found that such methods are less effective for deep-seated attitudes, such as those relating to politics. In fact, imagining the perspectives of out-group members can even backfire and hinder subsequent attitude change.…”
Section: Choice Blindness As a Methods To Study Depolarizationmentioning
confidence: 99%
“…However, caution is needed when considering techniques to bridge the divide. One tempting solution—encouraging sides to consider the opposition’s perspective—can actually exacerbate differences in certain conditions (Catapano, Tormala, and Rucker 2019).…”
Section: Opportunity and Hope: A Guide For Researchmentioning
confidence: 99%